2015
DOI: 10.2514/1.j053535
|View full text |Cite
|
Sign up to set email alerts
|

Study Based on the AIAA Aerodynamic Design Optimization Discussion Group Test Cases

Abstract: Three model problems associated with aerodynamic drag minimizations are studied. These test cases have been proposed by the aerodynamic design optimization discussion group, and they include an inviscid NACA0012 nonlifting airfoil, a viscous RAE2822 lifting airfoil, and a viscous lifting wing based on the NASA Common Research Model. Various optimization methods are used, including MDOPT, TRANAIR, SYN83, and SYN107. The resulting designed and associated baseline geometries are cross analyzed by several computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Interestingly, the discrepancies in the solutions are quite localized. The double pressure recovery features are consistent with curves observed for this case by LeDoux et al 27 The presence of non-unique solutions in the design space explains the poor convergence of some of the optimizations. Analyses of other geometries using the different convergence paths were conducted, and while non-unique solutions were not always observed, they were found to be common.…”
Section: Optimization Resultssupporting
confidence: 89%
“…Interestingly, the discrepancies in the solutions are quite localized. The double pressure recovery features are consistent with curves observed for this case by LeDoux et al 27 The presence of non-unique solutions in the design space explains the poor convergence of some of the optimizations. Analyses of other geometries using the different convergence paths were conducted, and while non-unique solutions were not always observed, they were found to be common.…”
Section: Optimization Resultssupporting
confidence: 89%
“…The plot at y/b = 0.5024 shows that the optimizer is successful in eliminating the shock and and smoothing out the pressure recovery. The optimizer rotates the tail down one degree and reduces the overall drag by 2% relative to the baseline untrimmed geometry, a result which agrees well with Chen et al 9 and Ledoux et al 26 showed that geometries optimized for this problem can have non-unique flow solutions and poor o↵-design behaviour. A multi-point optimization is presented here for in an attempt to produce more robust airfoils.…”
Section: Resultssupporting
confidence: 82%
“…As such, the AIAA Aerodynamic Design Optimization Discussion Group (ADODG) a was formed. As part of this, a number of inviscid and viscous aerofoil and wing benchmark optimization cases were suggested, with a number of research groups presenting results; see [13][14][15][16][17][18][19][20][21] for example.…”
Section: Introductionmentioning
confidence: 99%